IMMERSIVE TECHNOLOGIES AS AN INNOVATIVE TOOL FOR PROJECTING IN DESIGN - Пашкевич, К. Л.; Воробчук , М. С.; Шинкар , А. Ю. (Art and Design, 2023)
The aim of the study is to determine the development of immersive technologies at the current stage; analyze current examples of the use of such technologies; find out the possibilities of using AR, VR, MR technologies in design and determine their prospects in creating visual content. Methodology. Analytical, sociocultural, structural approaches, as well as methods of information modeling and system analysis are applied. Results. An analysis of immersive technologies was carried out, and based on this, the most common technologies used in the design of design products were systematized and described. An analysis of literary sources on the topic of the study was carried out, a description of AR, VR, MR technologies was provided, the advantages and disadvantages of using augmented reality technology in design were determined. It has been established that immersive technologies, despite existing technical limitations, are a promising design tool that creates favorable conditions for the realization of designers' creative ideas. Scientific novelty. The possibility of using immersive technologies in various types of design was studied, the features of their application in practice were revealed. The advantages and disadvantages of the implementation of AR, VR, MR technologies in the design of design products have been revealed. Practical significance. The results of the research can be used for further study of immersive technologies, their application in design, as well as serve as theoretical and practical material for the training of design specialists and for writing scientific papers.